Factores de riesgo modificables que predisponen al desarrollo de la enfermedad de alzheimer. - Armijos Ajila, Cristina Johanna (Machala : Universidad Técnica de Machala, 2019)
Alzheimer's disease is the most frequent form of dementia, it is a progressive neurological disease in which the brain gradually wears out. It is estimated that 46.8 million people live with dementia in the world in 2015, more than 9.9 million new cases of dementia are reported every year in the world. Although scientists know that Alzheimer's disease involves a failure of nerve cells, the reason why this happens is still unknown. Among the modifiable risk factors of Alzheimer's disease, we have: diabetes, hypertension, obesity, tobacco and alcohol. At present there is no cure for this disease. But if several medications that can help with the symptoms. OBJECTIVE: To determine the modifiable risk factors that predispose to the development of Alzheimer's disease, through the descriptive analysis of scientific articles. METHODOLOGY: The methodology applied in this project is the revision of scientific articles, the same ones that have been identified in the pages such as: Pubmed, New England. CONCLUSIONS: Alzheimer's disease is a neurodegenerative pathology that leads to the wearing down of memory, creating a great personal, social and economic impact on those who suffer from it. By knowing the modifiable risk factors and how they predispose to the development of Alzheimer's, it gives us a guideline on how we can help prevent and delay the disease.
La enfermedad de Alzheimer es la forma más frecuente de demencia, es una enfermedad neurológica progresiva en la que el cerebro se desgasta de manera paulatina. Se estima, que 46.8 millones de personas viven con demencia en el mundo en el año 2015, se reporta más de 9.9 millones de casos nuevos de demencia cada año en el mundo. Aunque los científicos saben que la enfermedad de Alzheimer implica una falla de las células nerviosas, la razón por la cual esto ocurre es aún desconocida. Dentro de los factores de riesgo modificables de la enfermedad de Alzheimer tenemos: diabetes, hipertensión arterial, obesidad, tabaco y alcohol. En la actualidad no hay cura para esta enfermedad. Pero si varios medicamentos que pueden colaborar con los síntomas. OBEJTIVO: Determinar los factores de riesgo modificables que predisponen al desarrollo de la Enfermedad de Alzheimer, mediante el análisis descriptivo de artículos científicos. METODOLOGIA: La metodología aplicada en este proyecto es la revisión de artículos científicos, los mismos que se ha identificado en las páginas tales como: Pubmed, New England. CONCLUSIONES: La enfermedad de Alzheimer es una patología neurodegenerativa que acarrea el desgaste de la memoria, creando un gran impacto tanto personal, social y económico de quien la padece. Al conocer los factores de riesgo modificables y la manera de como predisponen al desarrollo del Alzheimer, nos da una pauta de cómo podemos ayudar a prevenir y retrasar la enfermedad.
Keywords: ALZHEIMER'S DISEASE; RISK FACTOR; NEURODEGENERATIVE DISEASE